Problems related to jurisdiction in the arbitration of the International Center for the Settlement of Investment Disputes (ICSID) - Yakovleva, И. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
Problems related to the jurisdiction of the ICUIS are extremely relevant, and errors made in the preparation of an arbitration clause may exclude the competence of the Center. When drafting a document defining the ICISD as a forum for the settlement of emerging disputes, it is necessary to carefully check the compliance of the document with the requirements of the Convention and international law. Deviation from the main criteria could result in the state accepting the investment invoking that the Centre does not have jurisdiction. The article discusses issues related to the jurisdiction of the ICSID in the consideration of investment disputes, as well as how non-compliance with the terms of jurisdiction may affect the implementation of the right to protect investments under the ICSID.